Respuestas

¡La mejor respuesta!
  • Usuario de Brainly
2014-01-13T23:29:31+01:00
A) 3x² - 5x + 2 = 0

x =  \frac{5 \frac{+}{}  \sqrt{(-5)^2-4*3*2} }{2*3}

x =  \frac{5 \frac{+}{}  \sqrt{25-24} }{6}

x =  \frac{5 \frac{+}{}  \sqrt{1} }{6}

x =  \frac{5 \frac{+}{}1 }{6}

x = (5 + 1)/6 = 6/6 = 1
x = (5 - 1)/6 = 4/6 = 2/3
Solución:
x = 1
x = 2/3


b) 
4x² + 3x - 22 = 0

x = \frac{-3 \frac{+}{} \sqrt{3^2-4*4*(-22)} }{2*4}

x = \frac{-3 \frac{+}{} \sqrt{9+352} }{8}

x = \frac{-3 \frac{+}{} \sqrt{361} }{8}

x = \frac{-3 \frac{+}{} 19 }{8}

x = (-3 + 19)/8 = 16/8 = 2
x = (-3 - 19)/8 = -22/8 = -11/4
Solución:
x = 2
x = -11/4


c) x² + 11 - 24 = 0
x
² - 13 = 0
x² = 13
x = √13
Solución: 
x = √13


d) x(x + 3) = 5x + 3 
x
² + 3x = 5x + 3
x² - 2x - 3 = 0

x = \frac{2 \frac{+}{} \sqrt{(-2)^2-4*1*(-3)} }{2*1}

x = \frac{2 \frac{+}{} \sqrt{4+12} }{2}

x = \frac{2 \frac{+}{} \sqrt{16} }{2}

x = \frac{2 \frac{+}{}4 }{2}

x = (2 + 4)/2 = 6/2 = 3
x = (2 - 4)/2 = -2/2 = -1
Solución:
x = 3
x = -1